Challenges in the Diagnosis of Medulloblastoma Recurrence at an Unusual Site in a Patient With Prader-Willi Syndrome. Issue 5 (July 2020) - Panagopoulou, Paraskevi; Sattar, Shaista; Aquilina, Kristian; Jan, Wajanat; Jacques, Thomas; Slater, Olga
Abstract : Medulloblastoma is the most common malignant pediatric brain tumor. Survival rates range between 50% and 80% depending on histology and other biologic features, metastases, and treatment approach. Prader-Willi syndrome (PWS) is a genetically inherited disorder characterized by dysmorphic features, mental retardation, obesity, and hypogonadism among other features. We describe a 10.5-year-old girl with PWS and previous standard-risk medulloblastoma that relapsed in the pons 3 years after the end of treatment. Diagnosis of relapse was delayed by a preceding varicella infection, an initial clinical/radiologic response to steroids and the unusual location, and was confirmed with a stereotactic biopsy. Second-line therapy was commenced, however, the patient rapidly deteriorated and died. This is the first report of medulloblastoma in a patient with PWS.